2021
DOI: 10.1111/bjep.12444
|View full text |Cite
|
Sign up to set email alerts
|

Investigating how autonomy‐supportive teaching moderates the relation between student honesty and premeditated cheating

Abstract: Background. Cheating at the post-secondary level is a skewed phenomenon. While personality and environmental factors are associated with cheating, few studies account for the zero inflation when predicting cheating behaviour.Aim. In this study, we explore a person-situation interaction hypothesis where teacher autonomy support (AS) could modify the relation between students' honesty trait and premeditated cheating.Sample. Participants were 710 college students and 31 teachers.Methods. Teacher and student repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Due to the nature of academic dishonesty behaviors, responses to Likert-type or frequency scales are usually skewed (fewer answers on the high-frequency than the low-frequency scale ends) and non-normally distributed. To accommodate non-normality, suitable non-parametric tests (e.g., Spearman-Rank correlation coefficient for associations, Wilcoxon-Mann-Whitney U test for group comparisons), or appropriate model distributions (e.g., poisson or (zero inflated) negative binomial regression models, e.g., Bureau et al, 2022;Patrzek et al, 2015) should be used. Another approach is to transform the (non-normal) academic dishonesty variable to allow the use of typical parametric tests.…”
Section: Analysis and Quantification Recommendationsmentioning
confidence: 99%
“…Due to the nature of academic dishonesty behaviors, responses to Likert-type or frequency scales are usually skewed (fewer answers on the high-frequency than the low-frequency scale ends) and non-normally distributed. To accommodate non-normality, suitable non-parametric tests (e.g., Spearman-Rank correlation coefficient for associations, Wilcoxon-Mann-Whitney U test for group comparisons), or appropriate model distributions (e.g., poisson or (zero inflated) negative binomial regression models, e.g., Bureau et al, 2022;Patrzek et al, 2015) should be used. Another approach is to transform the (non-normal) academic dishonesty variable to allow the use of typical parametric tests.…”
Section: Analysis and Quantification Recommendationsmentioning
confidence: 99%
“…Among multitudinous achievement emotions, enjoyment is commonly explored and has attracted much research attention due to its positive influence on learning ( Simonton and Garn, 2020 ; Zaccoletti et al, 2020 ), which are significantly associated with cognitive processes, motivational beliefs, and learning environment factors ( Pekrun, 2006 ; Schunk and Usher, 2019 ). Empirical studies largely support a close relationship between teacher autonomy support and positive achievement emotions, i.e., reading enjoyment (e.g., Lazarides and Buchholz, 2019 ; Bureau et al, 2022a ). As part of reading motivation factors, reading enjoyment involves the enjoyment or satisfaction of curiosity individuals engaged in reading activities ( OECD, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are a wide range of factors that might influence adolescents’ reading competence, teacher autonomy support have indicated to be the most crucial exogenous factors in learning processes and reading achievement (e.g., Cheon et al, 2018 ; Quin et al, 2018 ). Autonomy supportive teachers might relinquish much control of students’ learning process, adopt structure and motivating style by providing multiple solution pathways with students for internalizing and externalizing problems ( Vansteenkiste et al, 2012 ; Bureau et al, 2022a ). A cornucopia of studies have confirmed the notion that teacher autonomy support is positively linked to students’ personal characteristics ( Bureau et al, 2022a ), emotional wellbeing ( Gilbert et al, 2021 ), dogged perseverance ( Reeve and Cheon, 2021 ), active learning engagement ( Olivier et al, 2020 ), and educational performance ( Guay et al, 2019 ), whereas teacher highly controlling is linked to students’ frustration of psychological needs, disengagement and low learning outcomes ( Aelterman et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%